Design Practice as a Method of Professional Orientation of Teenagers in the System of Supplementary Education - Mishina, Nadezda; Javgildina, Zilia; Mishina, Anastasia; Gainetdin Damirа; Belomoyeva, Olga (Journal of History Culture and Art Research, 2018)
The impact of the career orientation in the sphere of design for teenagers is primarily determined by the level of mastering of special artistic and graphic knowledge, skills and creative application of them in new educational conditions. For this purpose, it is necessary to raise the social significance of both the learning process itself and its results. The solution for this task is facilitated by the inclusion of teenagers in such teaching methods that are aimed at the systematic implementation of artistic and project activities. Design practice is the most effective among these methods. The effectiveness of the study was confirmed by the results of diagnosing the level of the career orientation of the teenagers in the experimental group after their inclusion in the educational process of design practice. We used a set of methods: 1) theoretical – analysis of educational, psychological, philosophical, art history literature, methods of scientific knowledge (analysis, synthesis, induction, deduction); 2) empirical – questioning, pedagogical observation, method of peer review, pedagogical experiment, generalization and systematization of empirical material, interpretation of the data obtained. As a result, we came to the following conclusion: design practice, aimed at increasing the level of professional orientation, stimulates teenagers’ need to develop their artistic and graphic skills, artistic literacy, socially relevant personal qualities necessary for their future profession in design.